The Perceptions of Global warming and Environmental Benefits of Biodiesel for Sustainable Energy Among High school Students in Jakarta - Bayazid, Erdawati (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The increased demand for energy, climate change, and energy security concerns has driven the research interest for the development of alternative fuel from plant origin. Biodiesel derived from plant oils, which include edible and non-edible oil have gained interest for the last two decades as alternative for diesel around the world. The purpose of this study was to determine the perceptions of high school students in Jakarta on the regarding renewable biodiesel. The study conducted a survey among twelve-grade. High school students studying in private schools in easten Jakarta in order toexplore their perceptions of biodiesel production from non eedible oil and edible oil for heat and power. A total of 20 item questionnaires were administeredto a total of 185 students in twelve grades. In addition, three open-endedquestions were asked of the students in order to determine their level of knowledge regarding biodiesel, and power stations. The study data were analyzed using the SPSS statistical package program. The study results revealed that, thestudents were of the perception that biodiesel use wouldreduce global warming, and that renewable energy sources areenvironment-friendly, non toxic and renewable.In addition, thestudents generally knew about biodiesel sources and their importance, although they lacked knowledge about certain aspects of biodiesel.The study recommends energy and educational policy makers to increase awareness of non edible and edible oil baseed bioenergy production among young students. In this respect, schools, parents, and media can also play an important role to engage young students in bioenergy related discussions.